Immune-Related lncRNAs to Construct Novel Signatures and Predict the Prognosis of Rectal Cancer - Xing, Xiao-Liang; Xing, Chaoqun; Huang, Zhi; Yao, Zhi-Yong; Liu, Yuan-Wu (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancers. Almost 1/3 of CRC are rectal cancer, and 95% of rectal cancers are rectal adenocarcinoma (READ). Increasing evidences indicated that long noncoding RNAs (lncRNAs) have important role in the genesis and development of cancers. The purpose of our present study was to identify the differential expression lncRNAs which potentially related with immune cells infiltration and establish a risk assessment model to predict the clinical outcome for READ patients. We obtained 3 immune related differential expression lncRNAs (IR-DELs) (C17orf77, GATA2-AS1 and TPT1-AS1) by differential expression analysis following correlation analysis and Cox regression analysis. A risk assessment model were constructed by integration these analysis results. Then we plotted the 1-, 3-, and 5-year ROC curves depending on our risk assessment model, which suggested that all AUC values were over 0.7. In addition, we found that the risk assessment model was correlated with several immune cells and factors. This study suggested that those 3 signatures (C17orf77, GATA2-AS1, and TPT1-AS1) screened by pairing IR-DELs could be prognosis markers for READ patients and might benefit them from anti-tumor immunotherapy.